Influence of partial root-zone saline irrigation management on tomato yield and fruit quality from a potted-plant study - Alves, Rita de Cássia [UNESP]; de Medeiros, Ana Santana; Nicolau, Mayara Cristina M. [UNESP]; Oliveira, Francisco de Assis; Lima, Leonardo Warzea; Aroucha, Edna Maria M.; Gratão, Priscila Lupino [UNESP] (My University, 2018)
This research aimed to evaluate the yield and quality of tomato plants under different managements of salt stress by adopting the partial root-zone saline irrigation (PRSI) system. The experiment was conducted in a greenhouse at the Universidade Federal Rural do Semi Árido (UFERSA), Mossoró, Rio Grande do Norte (RN), Brazil. The experimental design was completely randomized, with six treatments and four replicates, totaling 24 plots. The treatments consisted of six different irrigation management regimes using low and high saline water (S1–0.5 and S2–5.0 dS·m–1), applied with or without PRSI, such that one side of the root-zone was submitted to saline water whilst the other side was water low salinity irrigated. For treatments T1 (control), T2 (S2 water), and T3 (alternate irrigation system between S1 and S2, with a cycling period of 15 d for each one), the PRSI was not applied; T4 (irrigation with S1 and S2, adopting the PRSI system from phase II to phase IV), T5 (irrigation with S1 and S2 in phase II, alternating in phase III; in phase III the inversion of the remaining water was made until the end of phase IV), and T6 (irrigation with S1 and S2, adopting the PRSI system in phase II, with the water switched between low and high saline water every 15 days, remaining until the end of phase IV) treatments were under the PRSI. The number of fruit per plant, fruit weight, fruit longitudinal and transverse diameter, pulp firmness, soluble solids content, titratable acidity, pH, vitamin C, color relation (a*/b*), lycopene, and β-carotene were determined as parameters for the fruit yield and quality evaluation. Our findings reinforce the importance of the use of PRSI systems followed by irrigation managements without loss of product quality, such as demonstrated by T4 and T5 water managements.
Keywords: Lycopene; Salinity; Solanum lycopersicum; Water management